Comparison of different methods of measuring angle of progression in prediction of labor outcome. (2nd March 2020) - Frick, A.; Kostiv, V.; Vojtassakova, D.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objectives: First, to compare the manual sagittal and parasagittal and automated parasagittal methods of measuring the angle of progression (AoP) by transperineal ultrasound during labor, and, second, to develop models for the prediction of time to delivery and need for Cesarean section (CS) for failure to progress (FTP) in a population of patients undergoing induction of labor. Methods: This was a prospective observational study of transperineal ultrasound in a cohort of 512 women with a singleton pregnancy undergoing induction of labor. A random selection of 50 stored images was assessed for inter‐ and intraobserver reliability of AoP measurements using the manual sagittal and parasagittal and automated parasagittal methods. In cases of vaginal delivery, univariate linear, multiple linear and quantile regression analyses were performed to predict time to delivery. Univariate and multivariate binomial logistic regression analyses were performed to predict CS for FTP in the first stage of labor. Results: The intraclass correlation coefficient (ICC) for the manual parasagittal method for a single observer was 0.97 (95% CI, 0.95–0.98) and for two observers it was 0.96 (95% CI, 0.93–0.98), indicating good reliability. The ICC for the sagittal method for a single observer was 0.93 (95% CI, 0.88–0.96) and for two observers it was 0.74 (95% CI, 0.58–0.84), indicating moderate reliability for a single observer and poor reliability between two observers. Bland–Altman analysis demonstrated narrower limits of agreement for the manual parasagittal approach than for the sagittal approach for both a single and two observers. The automated parasagittal method failed to capture an image in 19% of cases. The mean difference in AoP measurements between the sagittal and manual parasagittal methods was 11°. In pregnancies resulting in vaginal delivery, 54% of the variation in time to delivery was explained in a model combining parity, epidural and syntocinon use during labor and the sonographic findings of fetal head position and AoP. In the prediction of CS for FTP in the first stage of labor, a model which combined maternal factors with the sonographic measurements of AoP and estimated fetal weight was superior to one utilizing maternal factors alone (area under the receiver‐operating‐characteristics curve, 0.80 vs 0.76). Conclusions: First, the method of measuring AoP with the greatest reliability is the manual parasagittal technique and future research should focus on this technique. Second, over half of the variation in time to vaginal delivery can be explained by a model that combines maternal factors, pregnancy characteristics and ultrasound findings. Third, the ability of AoP to provide clinically useful prediction of CS for FTP in the first stage of labor is limited. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.